Fas-Activated Serine/Threonine Kinase Governs Cardiac Mitochondrial Complex I Functional Integrity in Ischemia/Reperfusion Heart - Chen, Xiyao; Hu, Guangyu; Wang, Yuanyuan; Li, Congye; Zhang, Fuyang (Frontiers in Cell and Developmental Biology, 2021)
Cardiac energy homeostasis is strictly controlled by the mitochondrial complex-mediated respiration. In the heart, mitochondrial complex I is highly susceptible to functional and structural destroy after ischemia/reperfusion (I/R), thereby contributing to myocardial energy insufficiency and cardiomyocyte death. Fas-activated serine/threonine kinase (FASTK) is recently recognized as a key modulator of mitochondrial gene expression and respiration. However, the role of FASTK in cardiac I/R process is undetermined. Here, we show that FASTK expression was down-regulated in the post-I/R heart. The reactive oxygen species scavenger N-acetyl-L-cysteine reversed I/R-induced FASTK down-regulation. Genetic deletion of FASTK exacerbated I/R-induced cardiac dysfunction, enlarged myocardial infarct size, and increased cardiomyocyte apoptosis. Compared with the wild type control, the FASTK deficient heart exhibited a lower mRNA expression of NADH dehydrogenase subunit-6 (MTND6, a mitochondrial gene encoding a subunit of complex I) and was more vulnerable to I/R-associated complex I inactivation. Replenishment of FASTK expression via adenovirus-mediated gene delivery restored mitochondrial complex I activity and ameliorated cardiomyocyte death induced by I/R, whereas these beneficial effects were blocked by the co-treatment with rotenone, a specific complex I inhibitor. in vivo experiments further confirmed that cardiac overexpression of FASTK ameliorated I/R-related MTND6 down-regulation and mitochondrial complex I inactivation, thereby protecting the heart against I/R injury. Collectively, these data for the first time identify that the down-regulation of FASTK is a direct culprit behind the loss of mitochondrial complex I functional integrity and cardiac injury induced by I/R process. Targeting FASTK might be a promising and effective strategy for MI/R intervention.